Transformation and impact of higher education in Korea and Mexico - Rojo Velazquez, Gustavo Emilio (Universidad Autónoma de Tamaulipas, 2021)
This work provides a comparative exercise on the impact that higher education can have on the socio-economic development of two countries on different continents, Mexico and South Korea, and seeks to emphasize the role of human resources training and qualification as essential aspects for a country’s economic growth and social development. For this purpose, it describes the coverage indicators, the characteristics of both education systems, the investment of economic resources, the perception of educational quality, among others; some reflections are made upon them, the differences between the two educational sytems both in the field of educational policies implemented, as well as the transcendence, efficiency and effectiveness of these and their reflection in national indicators. This comparative analysis is further particularized, when considering a Korean university and a Mexican university focusing on the postgraduate course and its impact on the environment and productive life.